2018
DOI: 10.1111/1365-2745.13069
|View full text |Cite
|
Sign up to set email alerts
|

Ovule bet‐hedging at high elevation in the South American Andes: Evidence from a phylogenetically controlled multispecies study

Abstract: How animal‐pollinated plants support low and stochastic pollination in the high alpine is a key question in plant ecology. The ovule bet‐hedging hypothesis proposes compensation for stochastic pollination via ovule oversupply in flowers allowing the benefits of windfall pollination events to be reaped. Under this hypothesis, ovule number is expected to increase from tree line upward on high mountains characterized by steep declines in flower visitation rates and increasingly more variable pollination. Ovule/fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 141 publications
(238 reference statements)
1
18
1
Order By: Relevance
“…Arroyo & al. (2019), when studying the effect of elevation and phylogenetic relationships on ovule number in the southern Andes, included material from Valle Nevado (Region Metropolitana, Chile) in a phylogenetic analysis using ITS, which was identified as T. leichtlinii (based on the illustration in Baker, 1876). These plants correspond with other collections made by the authors in the same general area, here identified as T. sessile .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arroyo & al. (2019), when studying the effect of elevation and phylogenetic relationships on ovule number in the southern Andes, included material from Valle Nevado (Region Metropolitana, Chile) in a phylogenetic analysis using ITS, which was identified as T. leichtlinii (based on the illustration in Baker, 1876). These plants correspond with other collections made by the authors in the same general area, here identified as T. sessile .…”
Section: Discussionmentioning
confidence: 99%
“…Greene (Arroyo & al., 1981). The early flowering under the snow and the habitat of T. sessile have led to a paucity of botanical collections (but see Arroyo & al., 2019). Furthermore, the confusion associated with T. leichtlinii , in which the number of flowers per bract was described as plurifloral seems to be erroneous ( T. sessile is always unifloral), has contributed to taxonomic misidentifications of material that belongs to T. bivalve (we corroborated the identification of herbaria specimens).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outer flower diameter and total flower length were 3.3–6 cm (Mean = 4.8 cm) and 2.5–4.6 cm (Mean = 3.6 cm), respectively ( N = 30 on 26 plants). Ovule number per flower for the same population is 842.6 ± 66.14 (Mean ± 1 SE; Arroyo et al, 2019). As can be appreciated in Figure 1, the flowers contain a very large number of petaloid tepals.…”
Section: Methodsmentioning
confidence: 98%
“…Previous work showed the large flowers of E . curvispina contain by far the largest amount of dry biomass (475 mg) among 130 simple‐flowered species sampled (Arroyo et al, 2019), which is expected to translate into high per day maintenance costs. This finding raised the question as to whether the flowers of E .…”
Section: Introductionmentioning
confidence: 99%